The Impact of Pedagogical Competence on Students’ Learning Achievement under the Merdeka Curriculum - Amelia Lestari; Baso Jabu; Abdul Halim (International Journal of Language, Education, and Literature, 2024)
Pedagogical competence has become essential to be investigated because it directly relates to how the teachers facilitate the teaching and learning process, thus assisting students in accomplishing their learning objectives. This research aimed to describe the impact of EFL teachers’ pedagogical competence on students learning achievement under the Merdeka curriculum. This research was undertaken at SMPN 1 Sinjai, Sinjai Regency, South Sulawesi Province. This research used a qualitative method by using a case study design. The participants in this research were two EFL teachers who taught in seventh grade which were chosen purposively. The research instruments were observation, interview, and documentation. This research showed that the EFL teachers' pedagogical competence substantially positively impacts student learning achievement under the Merdeka curriculum. The researcher suggests that EFL teachers should actively develop their pedagogical competence to create and produce effective learning centered on the students and schools also should provide supportive infrastructure, offer tailored professional development opportunities, align policies with the curriculum, engage parents and the community, and establish robust monitoring and evaluation systems.